THE EFFECT OF LEARNING STYLES ON THE CRITICAL THINKING SKILLS OF ELEMENTARY SCHOOL STUDENTS IN MATHEMATICS - Febrianti, Nurul; Suparjo, Suparjo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study describes the effect of learning styles on the critical thinking skills of elementary school students in Banyumas Regency, Central Java. The type of research used is field research with an ex post facto (survey) method, taking the research setting at Sokaraja Tengah Elementary School in Banyumas. The research sample used probability sampling with cluster sampling technique focused on 123 fourth-grade students. Data collection used a learning style questionnaire and critical thinking ability test. The data analysis technique used was Kruskal-Wallis non-parametric statistics because the data was not normally distributed. The Kruskal-Wallis result using a significance level of 0.05 and an Asymp. Sig. value of 0.004 < 0.05 indicates that there is a significant difference in critical thinking skills between students with different learning styles. Thus, the null hypothesis is rejected, meaning that there is an influence of learning style on the critical thinking skills of elementary school students in mathematics in Sokaraja Tengah Village, Banyumas.